Glimpsing the chemical composition and the potential of Myrtaceae plant extracts against the food spoilage fungus Thielaviopsis ethacetica. (April 2023) - Duarte, Jorge Andrés; Alves Ribeiro da Silva, Gabrielle; Machado, Francisco Paiva; Folly, Diogo; Peñaloza, Evelyn; Garrett, Rafael; Santos, Marcelo Guerra; Ventura, José Aires; Wermelinger, Guilherme Freimann; Robbs, Bruno Kaufmann; Rocha, Leandro; Fiaux, Sorele Batista
Highlights: Native Brazilian Myrtaceae species are promising against Thielaviopsis ethacetica fungus. Percentages of mycelial inhibition above 80% were observed. Promising Myrtaceae extracts inhibited conidial germination. 13 metabolites are annotated in the polar extract of Myrcia amazonica. Flavonoids are predominant in Myrciaria floribunda extract according to LC-HRMS/MS analysis.